2016
DOI: 10.24095/hpcdp.36.9.03
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight and obesity trends in Canada

Abstract: Introduction Excess weight is a key risk factor for chronic disease, and the systematic collection, analysis and reporting of key trends are important to surveillance of overweight and obesity. Methods We used univariate analyses to calculate current prevalence estimates of excess weight among Canadian children and youth. Results Almost 1 in 7 children and youth is obese. Rates vary based on sociodemographic factors such as age, sex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 9 publications
1
100
2
3
Order By: Relevance
“…In Canada, 18.3% of 6 to 17 year olds are considered overweight, and 13.1% are considered obese, accounting for 31.4% of Canada's child and adolescent population . Similarly, a high prevalence of obesity persists in the United States, including 20.6% of adolescents in 2013 to 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, 18.3% of 6 to 17 year olds are considered overweight, and 13.1% are considered obese, accounting for 31.4% of Canada's child and adolescent population . Similarly, a high prevalence of obesity persists in the United States, including 20.6% of adolescents in 2013 to 2014 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews that reported equivocal associations between childhood obesity and crime or perceived safety may have been limited by including studies of all children under the age of 18 years. Given that rates of obesity have been shown to increase through childhood and adolescence in both the USA and Canada , combining groups of children across ages may increase the risk of spurious results. Furthermore, many studies of the association between childhood obesity and neighbourhood crime or perceived safety report continuous BMI or BMI z ‐scores rather than applying a weight classification system and reporting on risk of obesity .…”
Section: Discussionmentioning
confidence: 99%
“…This framework considers individual risk and protective factors (sociodemographic, lifestyle, psychosocial and early-life) through the lens of the life stage, levels of influence and environments in which these factors play a role ( Figure 1). Building upon our recent reporting on trends in and sociodemographic factors associated with childhood obesity in Canada, 2 this work illustrates the remaining (lifestyle, psychosocial and early-life) risk and protective factors shown in this surveillance framework. This integrated appraisal of factors also links to childhood obesity reporting included in the Chronic Disease and Injury Indicator Framework (CDIIF), 4 which is an important PHAC resource to guide research, programs and policy in Canada.…”
Section: Introductionmentioning
confidence: 86%
“…20 Notably, guideline adherence appears to decrease with age (Table 1), while weight increases with age, as described in our earlier article. 2 Sedentary behaviours, such as watching TV, playing passive video games and using a computer, have been associated with obesity. 21 Canadian children and youth engage in an average of 8.4 hours (95% CI: 8.3-8.5) of sedentary activity each day.…”
Section: All-movement Behavioursmentioning
confidence: 99%
See 1 more Smart Citation